Post-thaw dilution of Rhamdia quelen sperm improves the reproductive success - França, Thales de Souza; Gomes, Itamar Cossina; Sanches, Eduardo Antônio [UNESP]; Atehortúa, Maritza Pérez; Teixeira, Nathalia Santos; Rodrigues, Rômulo Batista; de Freitas, Thaiza Rodrigues; Galuppo, Andrea Giannotti; Quirino, Monike; Benato, Jhony Lisbôa; Machado, Thales Lysakowski Flores; Marques, Lis Santos; et al. (Elsevier, 2022)
The aim was to evaluate the effect of a post-thaw dilution of Rhamdia quelen sperm in 1.1% NaCl (325 mOsm kg-1; pH 7.6; 24 °C) solution on the quality and reproductive capacity. Sperm from eight males were cryopreservation in nitrogen vapor at − 170 °C for 18 h in 0.25 mL straws in a freezing medium containing 5% fructose, 5% Powdered milk, and 10% methanol. The samples were thawed and post-thaw diluted (1:20) in NaCl solution or not (control). The higher spermatozoa velocities were observed in the post-thaw diluted samples (curvilinear (VCL) - 69 ± 11 µm s-1; average path (VAP) - 45 ± 8 µm s-1; straight-line (VSL) - 43 ± 8 µm s-1) compared to the control (VCL - 47 ± 10 µm s-1; VAP - 31 ± 6 µm s-1; VSL - 30 ± 6 µm s-1). Greater straightness (STR), progression (PROG), and beat cross frequency (BCF) were observed in the post-thaw diluted samples (STR - 96 ± 7%; PROG - 666 ± 128 µm; BCF - 42 ± 2 Hz) than in control (STR - 95 ± 5%; PROG - 463 ± 92 µm; BCF - 40 ± 2 Hz). The strongly curled tail was the only morphology change that differ between the post-thaw diluted (5 ± 2%) and control (2 ± 1%). Membrane integrity, mitochondrial activity, and normal larvae rate were not different between treatments. Fertilization and hatching were higher in the post-thaw diluted sperm (93 ± 3%; 82 ± 9%) when compared to control samples (65 ± 13%; 55 ± 17%). Were used oocytes from one female, limiting these results. The post-thaw dilution improved the sperm kinetics and reproductive parameters. Thus, this methodology can be included in the sperm cryopreservation protocol for R. quelen.
Keywords: Artificial fertilization; Hatching; South American silver catfish; Sperm cryopreservation; Sperm dilution; Sperm quality